1996
DOI: 10.1007/s002689900017
|View full text |Cite
|
Sign up to set email alerts
|

Papillary Thyroid Carcinoma in Mexican Patients: Clinical Aspects and Prognostic Factors

Abstract: The present study characterizes papillary thyroid carcinoma (PTC) in a Mexican patient sample and evaluates potential prognostic factors for recurrence. Clinical records of 229 patients with PTC were analyzed. Surgical specimens were rereviewed and DNA ploidy determined. Cox logistic regression was used to explore prognostic factors. Mean age +/- SD of the patients was 42 +/- 16 years, with a male/female ratio of 24:205. A thyroid mass was the initial manifestation in 99%. Extrathyroid invasion occurred in 45%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…AMES has marked tumor size more than 5 cm as high risk and UICC set two cut of at 2 and 4 cm [25,27]. Most of the recent studies have set the cut of at 3-4 cm according to prognosis of PTC patients [25,[27][28][29][30]35]. …”
Section: Categories Of Thyroid Malignanciesmentioning
confidence: 99%
“…AMES has marked tumor size more than 5 cm as high risk and UICC set two cut of at 2 and 4 cm [25,27]. Most of the recent studies have set the cut of at 3-4 cm according to prognosis of PTC patients [25,[27][28][29][30]35]. …”
Section: Categories Of Thyroid Malignanciesmentioning
confidence: 99%
“…To date, many studies have demonstrated that old age significantly affected the CSS of PTC patients, by setting the cutoff age at 40-55 yrs [13,[46][47][48][49][50][51][52][53][54][55]. We also showed that CSS showed a tendency similar to distant recurrence-free survival (40s vs. 50s, p = 0.0138): 50s vs. 60s, p < 0.0001: 60s vs. 70s, p = 0.0060) [23].…”
Section: B Cause-specific Survival (Css) Of Patientsmentioning
confidence: 99%
“…17,18 In papillary carcinoma, 63 of 123 cases showed high expression of delta Np73, but its expression level was significantly decreased in cases showing larger tumour, advanced patient age, massive extrathyroid extension and the presence of clinically apparent node metastasis. Since these parameters have been recognised as prognostic factors of patients with papillary carcinoma, [11][12][13][14] it is suggested that the delta Np73 expression level is even higher in patients with mild characteristics and with favorable prognosis. Furthermore, 70% of microcarcinomas, most of which grow slowly or not at all, 10 expressed a high level of delta Np73, indicating that this protein is not likely to significantly contribute to cell proliferation.…”
Section: Discussionmentioning
confidence: 98%
“…10 However, cases demonstrating aggressive features or risk factors such as advanced patient age, large tumour, massive extrathyroidal extension, and clinically apparent nodal metastasis (metastatic node, which is palpable or detected by preoperative ultrasonography) can show a dire prognosis. [11][12][13][14] Furthermore, once papillary or follicular carcinomas dedifferentiate, they are called anaplastic (undifferentiated) carcinoma and display extremely rapid growth with a dire prognosis. 15 To date, there is one manuscript reporting a high level of delta Np73 expression in thyroid carcinoma, 16 but the number of cases in this series is small for evaluating the role of this transcript in the progression of this carcinoma.…”
Section: Introductionmentioning
confidence: 99%